Security First - Amr G. E. Sabet (International Institute of Islamic Thought, 2009)
Couched in moral language and endeavoring to preempt possible shifts in foreign policy attitudes, this six-part book attempts to subtly and indirectly weave Israeli interests into American policy and upcoming decision-making processes. Essentially, it repackages Israel’s “security for peace” formula with the language of security (read “order”) and democracy (read “justice/ law”) and stresses the former’s priority over the latter – security being Israel’s paramount claim. In so doing, Etzioni seeks to limit references to Israel to give the reader the impression that he is dealing with issues over and beyond – a form of reorienting the reader’s attention through focal deception while “playing the same tune – on a different instrument” (p. xii). The book’s main thesis is that there are “principled” and “pragmatic” reasons forWashington to transform its foreign policy approach from prioritizing the spread of democracy to security (p. xi), for democracy must follow the establishment of “basic security” (p. xi) as the supreme human good. Doing things differently simply reflects the “Multiple Realism Deficiency Disorder” from which American foreign policy suffers (p. xiv), namely, a psychological state that deals with matters as Americans would like them to be rather than as they are (p. xv) ...